Ulcerative Colitis Is Under Dual (Mitochondrial and Nuclear) Genetic Control. Issue 4 (April 2016) - Rosa, Alexandra; Abrantes, Patrícia; Sousa, Inês; Francisco, Vânia; Santos, Patrícia; Francisco, David; Xavier, Joana M.; Oliveira, Sofia A.
Abstract : Background: Cellular oxidative stress and genetic susceptibility have been implicated in the multifactorial etiology of ulcerative colitis (UC). The nuclear genome association with UC has been intensely investigated, but the role of the mitochondrial DNA (mtDNA) has received far less attention and may account for part of the missing heritability. This study is a comprehensive analysis of the mtDNA contribution to UC susceptibility. Methods: The association of mitochondrial single-nucleotide polymorphisms (mtSNPs) and haplogroups with UC was tested in 488 cases and 833 controls of European ancestry from the NIDDK IBD Genetics Consortium Ulcerative Colitis Genome-Wide Association Study available through dbGaP and from the Illumina Genotype Control Database (studies 64 and 65). Results: No evidence of population stratification could be detected using 218 ancestry informative markers for European Americans. Seven of the 58 tested mtSNPs were nominally associated with UC, and A10550G in MT-ND4L withstands the Bonferroni correction ( P = 1.29E-06, odds ratio [ORG ] [95% confidence interval (CI)] = 4.80 [2.54–9.05], 10550G allele: 8.1% of patients and 1.9% of controls). A10550G remains equally associated after conditional analyses on the 11 UC genome-wide association studies (GWAS) top SNPs (6.35E-07 < P cond < 4.58E-06), which suggests that it constitutes an independent risk factor from nuclear-encoded susceptibility loci . We detected additive (but not multiplicative) epistatic interactions between A10550G and all 11 top GWAS hits. Subhaplogroup K1 ( P = 0.021, OR [95% CI] = 1.71 [1.08–2.69]) increased the risk for UC, whereas the U5b lineage conferred protection ( P = 0.016, OR [95% CI] = 0.34 [0.14–0.82]). Conclusions: These results suggest that UC has a dual mitochondrial and nuclear genetic control that warrants further replication in independent data sets and reinforces its etiopathogenic complexity. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 1 March 2016.